Integrating indicators of education quantity and quality in six francophone African countries - Adaiah, Keren Lilenstein (School of Economics, 2016)
Research and policy-making in education have historically focused on quantitative measures of education when assessing the state of education across countries. Recently, large-scale cross-national tests of cognitive skills have emerged as one way of moving beyond mere quantitative indicators of education, and instead allow researchers to incorporate qualitative elements of education, most notably what students know and can do. Notwithstanding the above, research and development initiatives too often assess these complementary aspects separately, which can lead to biased conclusions. To resolve this issue, the research presented here follows the method developed by Spaull and Taylor (2015) and provides composite measures of educational quantity (grade completion) and quality (learning outcomes) for six Francophone African countries. These composite measures are termed access to literacy and access to numeracy for literacy and numeracy rates respectively. This work also explores quantity and quality indicators separately to ascertain whether problems of access to schooling, or problems of quality among those already enrolled, is a more pertinent development issue. Finally, this work also contributes to understanding the extent and nature of inequalities, by looking at gender and socioeconomic status groups separately when considering (1) access, (2) learning outcomes, and (3) a composite measure of access and learning. Results of this work point to an education crisis within these African countries where both non-enrolment and a lack of learning within schools are contributing to dismal educational outcomes, even at the grade 2 level but especially at the grade 5 level. For example, only 18% and 25% of the grade 5 cohort investigated have access to literacy and access to numeracy, respectively, in Togo. Furthermore, inequality within socioeconomic groups is extremely large resulting in near zero estimates of competency levels for the most economically disadvantaged in some countries. Gender discrimination is dwarfed by economic discrimination but mean estimates suggest that while educational opportunities are similar for males and females at a grade 2 level, gender discrimination may already be visible at the grade 5 level.